Up-regulation of COX-2/PGE2 by endothelin-1 via MAPK-dependent NF-κB pathway in mouse brain microvascular endothelial cells - Chih‐Chung Lin; Hsi‐Lung Hsieh; Ruey‐Horng Shih; Pei‐Ling Chi; Shin‐Ei Cheng; Chuen‐Mao Yang (2013)
Endothelin-1 (ET-1) is a proinflammatory mediator and elevated in the regions of several brain injury and inflammatory diseases. The deleterious effects of ET-1 on endothelial cells may aggravate brain inflammation mediated through the regulation of cyclooxygenase-2 (COX-2)/prostaglandin E2 (PGE2) system in various cell types. However, the signaling mechanisms underlying ET-1-induced COX-2 expression in brain microvascular endothelial cells remain unclear. Herein we investigated the effects of ET-1 in COX-2 regulation in mouse brain microvascular endothelial (bEnd.3) cells.The data obtained with Western blotting, RT-PCR, and immunofluorescent staining analyses showed that ET-1-induced COX-2 expression was mediated through an ETB-dependent transcriptional activation. Engagement of Gi- and Gq-protein-coupled ETB receptors by ET-1 led to phosphorylation of ERK1/2, p38 MAPK, and JNK1/2 and then activated transcription factor NF-κB. Moreover, the data of chromatin immunoprecipitation (ChIP) and promoter reporter assay demonstrated that the activated NF-κB was translocated into nucleus and bound to its corresponding binding sites in COX-2 promoter, thereby turning on COX-2 gene transcription. Finally, up-regulation of COX-2 by ET-1 promoted PGE2 release in these cells.These results suggested that in mouse bEnd.3 cells, activation of NF-κB by ETB-dependent MAPK cascades is essential for ET-1-induced up-regulation of COX-2/PGE2 system. Understanding the mechanisms of COX-2 expression and PGE2 release regulated by ET-1/ETB system on brain microvascular endothelial cells may provide rationally therapeutic interventions for brain injury or inflammatory diseases.